Refractory Torsades de Pointes Due to Dofetilide Overdose - James Crosby DO; Huzefa Bhopalwala MD; Amrin Kharawala MD; Nakeya Dewaswala MD; Subramanya Shyam Ganti MD, MBBS; Adnan Bhopalwala MD (SAGE Publishing, 2021)
Dofetilide, a class III antiarrhythmic, is widely used in the treatment of cardiac arrhythmias. Antiarrhythmic drugs can have a long duration of action that prolongs the QT interval. This causes bradycardia that predisposes to R-on-T phenomenon subsequently leading to torsades de pointes (TdP). This necessitates constant monitoring to prevent or treat ventricular arrhythmias or bradycardia associated with cardiac medications. Although extremely rare, dofetilide overdose has been described in the literature. However, no evidence found in the current literature required prolonged intervention after the initial acute stabilization, leading to scarcity of data for treatment of ongoing dofetilide overdose. We present the case of an intentional dofetilide overdose in a 61-year-old Caucasian woman with a history of congestive heart failure, atrial fibrillation, stage IIIb chronic kidney disease, diabetes mellitus type II, hypothyroidism, morbid obesity, and hypertension that required extensive interventions for refractory TdP that lasted 4 days. Therapeutic as well as excess dosage of dofetilide can lead to TdP, which is usually controlled by decreasing the dose or terminating drug administration. If the arrhythmia is not resolved, guidelines recommend management with activated charcoal if ingestion is within 15 minutes, followed by administration of 2 g IV (intravenous) magnesium and addressing the electrolyte imbalance. However, if the arrhythmia is persistent due to ongoing dofetilide toxicity, isoproterenol is given as a bridge to overdrive pacing and dopamine is used as an alternative to isoproterenol.